Meter in Contemporary Jazz. A Practitioner-Based Approach - Orco, Andres (Revue musicale OICRM, 2025)
Jazz has a strong groove-based tradition that uses a stable meter and exhibits a significant degree of metric dissonance. Recently, the prevalence of metric multivalence stemming from conflicting acoustic signals has risen exponentially. This phenomenon, historically manifested between an improvisor’s solo and the piece’s repeating formal structure, has also become an aesthetic feature of the composition itself. In this essay, I highlight contemporary jazz pieces that afford listeners multiple metric interpretations and often lead to considerably different approaches to structure and groove. I propose an ecologically valid analysis that more closely aligns with the way practitioners approach the repertoire, and I demonstrate how these techniques build upon the Afro-diasporic and improvisational tradition of jazz. I contextualize these developments with an ethnographic study where I interviewed fifteen professional jazz musicians, uncovering consistent thought processes, musical training, and performance practices that appear foundational to develop an enculturated understanding of contemporary jazz.